A sociology of crime - Hester, Stephen (Routledge, Francis & Taylor Group, 2017)
Sociology -- Positively undertaken -- State -- Society -- Interpretatively turned -- Claims-making -- Defining the situation -- Practical reasoning -- Politically challenged -- Class -- Gender -- Race -- Epistemically undermined -- Power -- People? -- Conclusion